Melatonin Is Involved in Regulation of Bermudagrass Growth and Development and Response to Low K+ Stress - Chen, Liang; Fan, Jibiao; Hu, Zhengrong; Huang, Xuebing; Amombo, Erick; Liu, Ao; Bi, Aoyue; Chen, Ke; Xie, Yan; Fu, Jinmin (Frontiers in Plant Science, 2017)
Melatonin (N-acetyl-5-methoxytryptamine) plays critical roles in plant growth and development and during the response to multiple abiotic stresses. However, the roles of melatonin in plant response to K+ deficiency remain largely unknown. In the present study, we observed that the endogenous melatonin contents in bermudagrass were remarkably increased by low K+ (LK) treatment, suggesting that melatonin was involved in bermudagrass response to LK stress. Further phenotype analysis revealed that exogenous melatonin application conferred Bermudagrass enhanced tolerance to LK stress. Interestingly, exogenous melatonin application also promoted bermudagrass growth and development at normal condition. Furthermore, the K+ contents measurement revealed that melatonin-treated plants accumulated more K+ in both shoot (under both control and LK condition) and root tissues (under LK condition) compared with those of melatonin non-treated plants. Expression analysis indicated that the transcripts of K+ transport genes were significantly induced by exogenous melatonin treatment in bermudagrass under both control and LK stress conditions, especially under a combined treatment of LK stress and melatonin, which may increase accumulation of K+ content profoundly under LK stress and thereby contributed to the LK-tolerant phenotype. In addition, we investigated the role of melatonin in the regulation of photosystem II (PSII) activities under LK stress. The OJIP curves were obviously higher in plants grown in LK with melatonin (LK+Mel) than those of plants grown in LK medium without melatonin application for one or two weeks, suggesting that melatonin plays important roles in PSII against LK stress. After a combined treatment of LK stress and melatonin, the values for performance indexes (PIABS, PITotal and PICS), flux ratios (φP0, ΨE0 and φE0) and specific energy fluxes (ETO/RC) were significantly improved compared with those of LK stress alone, suggesting that melatonin plays positive roles in protecting PSII activity under LK stress. Collectively, this study reveals an important role of melatonin in regulating bermudagrass response to LK stress.